CONTRIBUTION OF CAMPUS TEACHING PROGRAMS IN IMPROVING THE STUDENTS’ NUMERACY LITERACY COMPETENCE IN PARTNER SCHOOL - Acep Musliman; Fitri Damayanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
The research in this paper was conducted on Campus Teaching 5 (KM5) activities as a form of Independent Learning Campus Merdeka (MBKM) in partner schools. It aims to provide opportunities for students to carry out activities outside the lecture class as a self-development experience. The research aims to determine the effectiveness of increasing literacy, numeracy, and students’ character as a result of the transformation conducted by students in campus teaching activities toward the quality improvement of learning services in partner schools. The expected transformation is an increase in literacy, numeracy, and students’ character competencies through a learning process that is innovative, creative, and fun. The research was conducted by using mixed methods between quantitative and qualitative descriptive methods. The research data were obtained from weekly reports of students’ activities at the assisted school as a partner school, namely Perti Islamic Private Elementary School in West Jakarta. Two types of data are weekly reports, which are qualitative and quantitative data based on the results of the Pretest and Posttest Minimum Competency Assessment (AKM). Based on the results of qualitative data analysis of weekly reports, the transformation process has an impact on improvement changes in literacy, numeracy, and students’ character competencies. It is also shown from the results of the AKM, there is a positive difference in the mean score of pre-test and post-test. It means that there is a competence improvement in literacy, numeracy, and students’ character. Hence, it can be said that the Teaching Campus is effective in improving students' literacy, numeracy, and students’ character competencies.